2018
DOI: 10.1186/s41601-018-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated control for voltage regulation of distribution network voltage regulation by distributed energy storage systems

Abstract: With more and more distributed photovoltaic (PV) plants access to the distribution system, whose structure is changing and becoming an active network. The traditional methods of voltage regulation may hardly adapt to this new situation. To address this problem, this paper presents a coordinated control method of distributed energy storage systems (DESSs) for voltage regulation in a distribution network. The influence of the voltage caused by the PV plant is analyzed in a simple distribution feeder at first. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 18 publications
0
44
1
Order By: Relevance
“…Voltage and frequency of the microgrid in islanded mode does not depend on the main grid. They can be controlled independently [87][88][89][90][91]. Wind turbine, solar system, biomass and many other renewable energy sources act as a prime mover of microgrid.…”
Section: Microgridmentioning
confidence: 99%
“…Voltage and frequency of the microgrid in islanded mode does not depend on the main grid. They can be controlled independently [87][88][89][90][91]. Wind turbine, solar system, biomass and many other renewable energy sources act as a prime mover of microgrid.…”
Section: Microgridmentioning
confidence: 99%
“…Optimal allocation of multiple CES system in active distribution network for economic assessment has been done in Liu et al 26 Optimal design of community battery energy storage through discrete continuous particle swarm optimization considering the impact of prosumers has been discussed in El-Batawy and Morsi. 27 The problem of rise in neutral voltage due to unbalanced allocation of solar power and loads has been mitigated with CES as discussed in Alam MJE et al 28 A coordinated control scheme for voltage regulation of distribution network via DES system has been studied in Zhang et al 29 However, the impact of CVR has not been explored with DES. The study reported in previous works 30,31 reveals that the significant power saving can be achieved in the presence of CES in VVO solution.…”
Section: Related Workmentioning
confidence: 99%
“…where Q p cb is reactive power supplied, Sw p cb is the number of switching step, Δq p cb is step variation of reactive power in each step, and Sw p,max cb maximum switching step of pth CB, respectively. • Voltage constraints: voltage profile of distribution feeder should be maintained within limits as shown in Equation (29).…”
Section: System Constraintsmentioning
confidence: 99%
“…A major aspect of this is achieved by modifying the inverter controller and utilizing the reactive power control capabilities of PV inverter. Conventionally, the Reactive Power‐Voltage (Q‐V) droop control and power factor control methods were adapted as PV inverter control strategies. In addition, an approach of combining multiple PV inverters is performed in Ref.…”
Section: Introductionmentioning
confidence: 99%